Amplicon metagenome comparison of Tandag River, Surigao del Sur, Philippines, based on high-throughput parallel DNA sequencing analysis of bacterial communities - ROXAN G. EUPEÑA-CARAY; GISELLE B. RAMOS; JOCELYN B. PANDUYOS; LUZMINDA S. BACQUIAL; SHARON ROSE M. TABUGO (Society for Indonesian Biodiversity, 2024)
Abstract. Eupeña-Caray RG, Ramos GB, Panduyos JB, Bacquial LS, Tabugo SRM. 2024. Amplicon metagenome comparison of Tandag River, Surigao del Sur, Philippines, based on high-throughput parallel DNA sequencing analysis of bacterial communities. Biodiversitas 25: 3464-3472. Rivers serve as a vital freshwater reservoir for the environment and human consumption. Biomonitoring based on eDNA is essential for aquatic ecosystems. The present study investigates the bacterial taxonomic diversity of this ecosystem using the V1-V3 16S rRNA regions obtained from paired-end Illumina MiSeq reads. A total of nine amplicon libraries (U1, U2, U3, M1, M2, M3, D1, D2, D3) were constructed corresponding to the sites (U-upstream, M-midstream, D-downstream) of the Tandag River. After post-quality control and processing, there were 608,099 amplicon sequence variants (ASVs), representing 1194 families and 2090 genera. Results showed that the most abundant ASVs were affiliated with genera Bacillus, Pseudomonas, Ralstonia, Alcaligenes, and Pseudarcicella, along with unclassified bacteria derived from Gammaproteobacteria, Alphaproteobacteria, Verrucomicrobia subdivision, Flavobacteria, and Pseudomonadaceae. The bacterial alpha diversity was ranked upstream>midstream>downstream. An increase in the abundance of Bacillus (Firmicutes) and Gammaproteobacteria in an urbanized zone indicated a high level of human activity and an important threat to public health. Noteworthy is that the alkaline environment characterized by increased pH levels favors the occurrence of alkaliphilic bacteria. Microbial community structure was influenced by anthropogenic interference and selective pressure from loads of urban discharge in the area. The functional prediction of bacterial communities by Parallel-Meta Suite (PMS) using the PICRUSt algorithm suggests functions related to metabolism and environment information processing. The presence of xenobiotic biodegradation bacteria highlights future possible applications. Findings contribute to understanding microbial communities in response to rapid urbanization. This is the first account of high-throughput sequencing analysis of bacterial communities in an urban river under anthropogenic stress in the Philippines.